Answer is BF...hope this helps
Answer:
58.3333333333
Step-by-step explanation:
Answer:
13
Step-by-step explanation:
4 + 3(x + 5)=5 x - 7
3x + 19=5x - 7
3x + 19 - 19=5x - 7 - 19
3x =5x - 26
3x - 5x=5x - 26 - 5x
-2= -26
-2x/-2 = -26/-2
x= 13
It might be wrong. I may have made a mistake with typing sorry.
Hope this helps a bit.
= a^21b^24c^10
use the product rules for each set of () then multiply them together. when multiplying variables with exponents you just add them together like for a^3 * a^5 = a^8. (a^3 b^12 c^2)^2 = (a^6 b^24 c^4)
Answer:
go to this link
Step-by-step explanation:
Videos
2:41
Manipulating expressions using structure (example 2) (video)